Turning a Blind Eye: Experimental Evidence of Partisan Bias in Attitudes Toward Corruption. (December 2013) - Anduiza, Eva; Gallego, Aina; Muñoz, Jordi
This article considers how partisanship conditions attitudes toward corruption. Stirred by the puzzle of why corruption does not seem to have the electoral consequences we would expect, it explores whether party supporters are more tolerant toward corruption cases when they affect their own party. The partisan-bias hypothesis is confirmed by a survey experiment carried out in Spain, a country where a number of corruption scandals have been recently visible. The results show that the same offense is judged differently depending on whether the responsible politician is a member of the respondent's party, of unknown partisan affiliation, or of a rival party. Furthermore, the degree of partisan bias depends on political sophistication. This suggests that although partisanship may induce tolerance to same-party corruption practices, the partisan bias disappears when political awareness is high.